Short-fed, grass-fed, and long-fed beef compared - Kropf, Donald H.; Allen, Dell M.; Thouvenelle, G.J. (Kansas State University. Agricultural Experiment Station, 2011)
Thirty carcasses, ten each from three groups-short-fed concentrate rations for about 70 days, grass-fed on Flint Hill pasture without supplemental feeding until slaughter in mid-to-late October, and long-fed concentrate rations at least 150 days-were used for taste-panel and display-color comparisons.
Keywords: Beef; Short-fed concentrate; Grass-fed concentrate; Long-fed concentrate